Effects of selected herbs and vegetables on the nutritional quality of beef burger and rat bioassay - Norhayati Mustafa Khalid,; Asma Qamaliah Abdul Hamid,; Chandrasena Ramakrishna,; Cheng, Irene; Chong, Zhi Yi; Ika Aida Aprilini Makbul,; Nur Amalina Abu Bakar,; Nurul Azrianti Abdul Aziz,; Nurul Hidayah A. Razak,; Nurul Huda Ngadimen,; Shariah Loh Long,; Abdul Salam Babji, (Penerbit Universiti Kebangsaan Malaysia, 2017)
Rat bioassay was used to evaluate the nutritional quality of beef burger as influenced by the addition of selected herbs and vegetables. The selected herbs and vegetables used were pucuk ubi (Mannihot esculenta), pucuk gajus (Anacardium occidentale), pegaga (Centella asiatica) and jantung pisang (Musa paradisiaca) as treatment group with casein and skimmed milk as reference. The rats were fed with herbs and vegetables at the rate of 0.5 (low dose) and 25 (high dose) g/kg body weight. The samples were analyzed for proximate analysis, protein quality and protein digestibility. The rats fed with pucuk ubi (high dose) (364.30 ± 25.34 g) indicated the highest mean of increased body weight (121.05 ± 14.65 g) while rats fed with skimmed milk (310.98 ± 18.92 g) showed the lowest mean increase in body weight (88.33 ± 14.25 g). As for the Protein Efficiency Ratio (PER) value, all the rats fed with herbs diet showed PER values that were significantly lower (p<0.05) compared to the casein. As for the in vivo apparent protein digestibility test, casein showed the highest digestibility value (86.33 ± 4.20) while pucuk gajus (high dose) (59.59 ± 5.41) showed the lowest. As for the in vitro digestibility analyses, casein indicated the highest value for in vitro digestibility (93.84 ± 0.33). Administration of herbs and vegetables at low and high doses show significant effects (p<0.05) on nutritional quality of beef burger. In conclusion, it was found that antinutritional factors in selected herbs and vegetables might affect the nutritional quality of beef burger.